Penyegaran Kader Posyandu tentang Pemantauan Pertumbuhan dalam Rangka Pencegahan Stunting di Desa Jabiren Kabupaten Pulang Pisau: Refreshment Posyandu Cadres on Growth Monitoring in the Stunting Prevention in Jabiren Village Pulang Pisau Regency - Widiastuti, Erma Nurjanah; Hapsari, Retno Ayu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Stunting is a chronic malnutrition problem characterized by a child's height being inappropriate for their age. Jabiren Village is one of the villages in Pulang Pisau Regency, the district with the fourth highest prevalence of stunted toddlers: 31.6%. The low ability, precision, and accuracy of data collected by cadres in carrying outweighing impacts inaccurate results of monitoring toddler growth. One effort to improve cadres' abilities and skills in carrying out anthropometric measurements is cadre refreshment. Community service activities aim to increase posyandu cadres' understanding of monitoring the growth of babies and toddlers in the context of preventing stunting in Jabiren Village, Pulang Pisau Regency. The target of this activity is the posyandu cadres for toddlers, totaling 20 people, with the method of carrying out activities using counseling lectures and question-and-answer methods. The evaluation design uses a pretest and posttest to see the increase in understanding of the N-Gain test. The results of community service activities show that the average knowledge score of cadres has increased from before and after being given a refresher on growth monitoring, namely 65.625 ± 16.16 to 84.375 ± 9.83. The percentage of cadre understanding regarding growth monitoring challenges is categorized as high, 20%, medium, 60%, and low, 20%. In conclusion, there was an increase in understanding of Jabiren Village Cadres.